2017
DOI: 10.1055/s-0043-103346
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LncRNA HOTAIR is Associated with Poor Prognosis in Thyroid Carcinoma: A Study Based on TCGA and GEO Data

Abstract: The role of long non-coding RNA (lncRNA) HOX transcript antisense RNA (HOTAIR) in thyroid carcinoma (TC) remains unclear. The current study was aimed to assess the clinical value of HOTAIR expression levels in TC based on publically available data and to evaluate its potential signaling pathways. The expression data of HOTAIR and clinical information concerning TC were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO), respectively. Furthermore, 3 online biological databases, Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 51 publications
(56 reference statements)
1
35
0
1
Order By: Relevance
“…With the advance on RNA-Seq technique and improvement of bioinformatics, numerous lncRNAs were detected and the representative RNA sequencing data of cancer was stored in TCGA database [ 26 , 27 ], which provided more clues for cancer detection and therapy. However, only a few lncRNAs had been further explored to fully understand the role in development, diagnosis, and therapy of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…With the advance on RNA-Seq technique and improvement of bioinformatics, numerous lncRNAs were detected and the representative RNA sequencing data of cancer was stored in TCGA database [ 26 , 27 ], which provided more clues for cancer detection and therapy. However, only a few lncRNAs had been further explored to fully understand the role in development, diagnosis, and therapy of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, a study investigated the involvement of 3 haplotype-tagging SNPs of HOTAIR in PTC and found that HOTAIR SNP (rs920778) was a PTC-susceptibility variant and further demonstrated that HOTAIR acts as an oncogene . A study based on TCGA and Gene Expression Omnibus data analysis showed that HOTAIR has been significantly overexpressed, associated with poor survival of thyroid cancer patients and likely to play a role in thyroid carcinogenesis via the Wnt signaling pathway (Li et al 2017b). These results suggest that HOTAIR is an onco-lncRNA and its overexpression could serve as a biomarker associated with poor outcome in thyroid cancer.…”
Section: Hotair (Hox Transcript Antisense Rna)mentioning
confidence: 98%
“…Furthermore, PTCSC1 and PTCSC2 were associated with thyroid cancer risk . HOTAIR overexpression has been associated with poor outcome (Li et al 2017b). LINC00271 and HIT000218960 have been associated with ETE, LNM, TNM stage III & IV and recurrence .…”
Section: Lncrnas: Prognostic Markers In Thyroid Cancermentioning
confidence: 99%
“…DAVID provides high-throughput functional annotation bioinformatics to perform functional annotation and enrichment analysis. e cutoff of recognized GO terms is set to FDR < 0.01 and KEGG pathways is set to P value <0.05 [26,27].…”
Section: Gene Ontology and Pathway Enrichment Analysismentioning
confidence: 99%